The Salivary Microbiota of Patients With Primary Biliary Cholangitis Is Distinctive and Pathogenic - Lv, Longxian; Jiang, Huiyong; Chen, Xiaoxiao; Wang, Qiangqiang; Wang, Kaicen; Ye, Jianzhong; Li, Yating; Fang, Daiqiong; Lu, Yingfeng; Yang, Liya; Gu, Silan; Chen, Jianing; et al. (Frontiers in Immunology, 2021)
The role of host-microbiota interactions in primary biliary cholangitis (PBC) has received increased attention. However, the impact of PBC on the oral microbiota and contribution of the oral microbiota to PBC are unclear. In this study, thirty-nine PBC patients without other diseases and 37 healthy controls (HCs) were enrolled and tested for liver functions and haematological variables. Saliva specimens were collected before and after brushing, microbiota was determined using 16S rDNA sequencing, metabolomics was profiled using Gas Chromatography-Mass Spectrometer (GC-MS), 80 cytokines were assayed using biochips, and inflammation inducibility was evaluated using OKF6 keratinocytes and THP-1 macrophages. Finally, the effect of ultrasonic scaling on PBC was estimated. Compared with HCs, PBC saliva had enriched taxa such as Bacteroidetes, Campylobacter, Prevotella and Veillonella and depleted taxa such as Enterococcaceae, Granulicatella, Rothia and Streptococcus. PBC saliva also had enriched sCD163, enriched metabolites such as 2-aminomalonic acid and 1-dodecanol, and depleted metabolites such as dodecanoic acid and propylene glycol. sCD163, 4-hydroxybenzeneacetic acid and 2-aminomalonic acid were significantly correlated with salivary cytokines, bacteria and metabolites. Salivary Veillonellaceae members, 2-aminomalonic acid, and sCD163 were positively correlated with liver function indicators such as serum alkaline phosphatase (ALP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT). PBC salivary microbes induced more soluble interleukin (IL)-6 receptor α (sIL-6Rα), sIL-6Rβ and tumour necrosis factor ligand superfamily (TNFSF)13B from OKF6 keratinocytes, and PBC salivary supernatant induced more IL-6, IL-10, granulocyte-macrophage colony-stimulating factor (GM-CSF), chemokine (C-C motif) ligand (CCL)13, C-X-C motif chemokine (CXC)L1 and CXCL16 from THP-1 macrophages. Toothbrushing significantly reduced the expression of inflammatory cytokines such as IL-1β, IL-8 and TNF-α and harmful metabolites such as cadaverine and putrescine in PBC but not HC saliva after P‐value correction. The levels of ALP and bilirubin in PBC serum were decreased after ultrasonic scaling. Together, PBC patients show significant alterations in their salivary microbiota, likely representing one cause and treatment target of oral inflammation and worsening liver functions.